FORMULASI ANTI-AGING CREAM POTASSIUM AZELOYL DIGLYCINATE TERHADAP STABILITAS FISIKA-KIMIA KRIM DENGAN VARIASI KONSENTRASI TRIETANOLAMIN SEBAGAI EMULGATOR - Sholichah Rohmani; Tyas Rahmadian Putri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Potassium-azeloyl-diglycinate is an active ingredient as a sebum normalizer and skin lightening-agent to moisturize and treat hyperpigmentation. Anti-aging (AA) cream is a cosmetic used to prevent premature aging. The use of an emulsifying agent is necessary to produce a stable cream. One of the commonly used emulsifying-agents is triethanolamine. This study aims to formulate the AA-cream potassium-azeloyl-diglycinate preparation varied with the concentration of triethanolamine. Potassium-azeloyl-diglycinate AA-cream is formulated in 3 formula variants using TEA, namely 1.5%,2%, and 2.5%. Physical-chemical stability testing was carried out before and after 6 storage cycles of cycling-test, including organoleptic-test, homogeneity, adhesion, spreadability, stability, emulsion-type, viscosity, pH, antioxidant activity, and hydration on the respondents’ skin. The test results show that formula 3 is the best formula for AA-cream. Meanwhile, the antioxidant activity tested using the DPPH-method showed that the three formulas had a very weak activity with values in Formula 1, 2, and 3 of 63,856 ppm, 57,508 ppm, and 45,640 ppm, respectively. The antioxidant-activity of the cream decreased after the storage of the cycling-test. The hydration-test on the skin on the back of the respondents’ palms showed an increase in moisture on the skin after applying it for 10 days.